ANALYSIS OF MEDAN STATE ADMINISTRATIVE COURT DECISION NUMBER 147/G/2023/PTUN-MDN ON THE WAQF LAND DISPUTE OF THE GRAND MOSQUE OF RANTAU PRAPAT FROM THE PERSPECTIVE OF FIQH SIYASAH - Syafi'i Ritonga; Khalid Khalid (Journal Analytica Islamica, 2026)
This study aims to analyze the decision of the Medan Administrative Court Number 147/G/2023/PTUN-MDN concerning the waqf land dispute of the Grand Mosque of Rantau Prapat from the perspective of fiqh siyasah. This research employs a normative juridical approach with qualitative methods through literature review of court decisions, waqf regulations, and Islamic legal literature. The findings reveal that waqf land disputes are mainly caused by weak administrative legality, particularly the absence of land certification, as well as suboptimal management by nazir. The court decision reflects the application of siyasah qadha’iyyah principles in balancing legal certainty, justice, and public benefit. However, the integration with maqāṣid al-sharī‘ah remains limited, especially in protecting waqf assets. This study highlights the importance of strengthening legal legitimacy through land certification, improving nazir professionalism, and adopting a progressive legal approach to achieve substantive justice.